Incidence trends of type 1 diabetes before and after the reunification in children up to 14 years of age in Saxony, Eastern Germany. - Ulf Manuwald; Peter Heinke; Eckhard Salzsieder; Janice Hegewald; Olaf Schoffer; Joachim Kugler; Thomas M Kapellen; Wieland Kiess; Ulrike Rothe (PLoS ONE)
Aims The aim of this study was to analyze the incidence rates of type 1 diabetes in Saxony before and after the German reunification. Methods The study examined two registries: one until 1990 and one since 1999. Only patients under 15 years of age with type 1 diabetes and living in Saxony were included in the study. Standardized incidence rates were described based on direct age standardization procedures using the Standard European Population for each calendar year between the observation periods 1982-1989 and 1999-2014. Age was grouped into three classes: 0-4, 5-9 and 10-14 years of age. Incidence data were presented as age-standardized incidence rates per 100,000 person-years (PY) with 95% confidence intervals [CI]. Joinpoint regression was used for trend analyses and Poisson regression was used to adjust for the effects of age and sex on the incidence. Results A total number of 2,092 incident cases of type 1 diabetes (1,109 males; 983 females) were included. The age-standardized incidence rates of type 1 diabetes per 100,000 PY was 7.9 [95%CI 6.8; 8.9] in the period from 1982-1989 and 20.1 [95%CI 14.0; 26.1] in the period from 1999-2014. The yearly increase in incidence over the entire time period (1982-2014) was 4.3% according to the average annual percent change (AAPC) method, and estimated to be 4.4% [95% CI 4.0; 4.8%] using a Poisson regression model adjusting for sex and age group. Conclusion In this study, a significantly increasing incidence of type 1 diabetes was observed after reunification. In future studies it would be interesting to follow up on the question of which environmental and lifestyle factors could be causing the increasing type 1 diabetes incidence.